How many ways can the letters in the word poster be arranged

Answers

Answer 1
Answer:

Answer:

720

Step-by-step explanation:

Answer 2
Answer:

Answer:

110

Step-by-step explanation:


Related Questions

Verify the identity. Show your work. (1 + tan2u)(1 - sin2u) = 1
The definition of an angle uses the undefined term ?
Which correctly gives the location of the point (18, 0)? A. x-axis B. y-axis C. Quadrant I D. Quadrant II
Jared recently purchased a new pair of running shoes. He got a 20% discount, which saved him $9.00
At a summer camp,the ratio of campers to adults is kept equivalent to 7:1 use equivalent ratios to complete the table

PLEASE HELP ME ASAP!! Solve the system of equations by substitution.Show Your Work
Y=2x-4
x+3y=4

Answers

the answer is x = 16/7

Which value of x makes the open sentence true?
5x – 6 = x + 12

Answers

The way we approach a problem like this is by using a technique called "collecting like terms".
This means that we want to put all of the values with an "x" on one side and all of the normal numbers on the other. For this particular problem we can do this as follows:
5x - 6 = x + 12
Now move the (- 6) to the right side of the equation by adding 6 to both sides:
=> 5x = x + 12 + 6
Now move the (x) to the left side of the equation by subtracting (x) from both sides:
=> 5x - x = 12 + 6
Now perform the simple arithmetic on both sides:
=> 4x = 18
Now remove the 4 from in front of the (x) by multiplying the whole equation by (1/4)
=> x = 18/4
Therefore to make your open sentence true, x must equal 18/4, or to simplify, 9/2, or as a decimal, 4.5. I hope this helped, and remember to try and understand not just the answer, but the maths involved in getting to the answer too :))

How do I do a question containing powers that are improper fractions?say for example 81 to the power of 3/2. thx

Answers

( 81 )^ ( 3 / 2 ) = ( 3 ^ 4 )^ ( 3 / 2 ) = 3 ^( 4 * 3 / 2 ) = 3 ^ 6 = 729.
81^{\tfrac{3}{2}}=\n(3^4)^{\tfrac{3}{2}}=\n3^{4\cdot\tfrac{3}{2}}=\n3^(2\cdot3)=\n3^6=\n729

A school bus has 25 seats, with 5 rows of 5 seats. 15 students from the first grade and 5 students from the second grade travel in the bus. How many ways can the students be seated if all of the second-grade students occupy the first row?a. 25P20
b. 5P5 × 20P15
c. 5C5 × 25C14
d. 5P5 × 15P15
e. 5P5 × 25C15

Answers

Answer:

The correct option is b.

Step-by-step explanation:

It is given that the school bus has 25 seats, with 5 rows of 5 seats.

The number of students from the first grade is 15 and the number students from the second grade is 5.

The formula to arrange r items in n places is

^nP_r=(n!)/((n-r)!)

The number of seats in first row is 5 and the number students from the second grade is 5. So, the total number of arrangement is

^5P_5

The number of seats except first row is 20 and the number students from the first grade is 15. So, the total number of arrangement is

^(20)P_(15)

The total number of ways the students can be seated if all of the second-grade students occupy the first row is

^5P_5* ^(20)P_(15)

Therefore the correct option is b.

Answer:

b

Step-by-step explanation:

plato fam

Evaluate.
5!/3!

answers
20
60
120

Answers

(5!)/(3!) = (5 * 4 * 3 * 2 * 1)/(3 * 2 * 1) = 5 * 4 = 20

The answer is A.

Answer:

It's 20 so the other person is correct

Step-by-step explanation:

Need a step by step on how to solve this please

Answers

I have not done this in advance.  I'm just going to write it down
and see what I can do with it:

[ 1/(x+3)² - 1/x² ] / 3


Multiply the top and bottom by (x+3)² :

[ 1 - (x+3)²/x² ] / 3 (x+3)²

Multiply the top and bottom by x² :

[ x² - (x+3)² ] / 3 x² (x+3)²

Now it's just a matter of expanding and cleaning things up,
and hope and pray that a lot of things cancel.

Eliminate the parentheses on top and bottom:

[ x² - x² - 6x -9 ] / 3 x² (x² + 6x + 9)

Combine the x² terms on top, and divide top and bottom by 3 :

[ - 2x - 3 ] / x² (x² + 6x + 9)

Finally, all I can make of this is:

- (2x + 3) / [ x(x+3) ]² .

That's not a whole lot prettier than the original form, but at least
we got rid of those fractions in the numerator of a fraction.

I hope this is some help to you.

((1)/((x+3)^2)-(1)/(x^2))/(3)=(1)/(3(x+3)^2)-(1)/(3x^2)=(x^2)/(3x^2(x+3)^2)-((x+3)^2)/(3x^2(x+3)^2)=(x^2-x^2-6x-9)/(3x^3(x+3)^2)\n\n=(-6x-9)/(3x^2(x+3)^2)=(3(-2x-3))/(3x^2(x+3)^2)=-(2x+3)/(x^2(x+3)^2)